Mozambique's Supplemental Land Tenure Survey, 2015 - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset is a supplemental data to Mozambique’s National Agricultural Survey (TIA) 2014. The purpose of the survey was to collect data on details of intra-household access to and control over land, land transfer (lease or inheritance) activities, household and farm-specific indicators of perceived tenure (in)security, and knowledge of the existing land law, which were not covered in TIA 2014. The survey covered a total of 3,556 households in seven (rural) provinces of Mozambique that were interviewed during TIA 2014. A structured household questionnaire was used to collect household, plot, and individual level data. Questionnaire modules related with access to land, land related legal knowledge, intra-household bargaining power were administered separately for the head and spouse. Hence, a detail gender dis-aggregated data was used to analyze the role social and economic transformations play in dictating the perceived tenure security of individuals with varying social status by comparing the within- and across-household differential effects.